Hate speech in Egyptian television talk shows: a qualitative study - Elias, Caroline (AUC Knowledge Fountain, 2020)
This research aims to examine hate speech in Egyptian talk shows. Firstly, the research examines how international and Egyptian frameworks deal with the doctrine of freedom of speech and expression in relation to the hate speech issue. Secondly, the research investigates the issue of hate speech in Egyptian talk shows through holding in-depth qualitative interviews with Egyptian media practitioners, media experts, and media policy and decision-makers. The hypothesis of the study is that the spread of hate speech in Egyptian talk shows is mostly intended to serve political and institutional agendas. Therefore, the data analysis examines how hate speech is understood in Egypt, the causes of this phenomenon, its effects on the Egyptian society as well as suggested solutions to combat it. According to the data analysis, the researcher has found that the major root causes of hate speech in Egyptian talk shows are social illiteracy as well as the confusion between the right to free speech and the practicing of hate speech. In addition, according to the data analysis, the hypothesis that hate speech in Egyptian talk shows occurs mostly due to political reasons, institutional corruption or personal agendas has been confirmed. Women, refugees, oppositionists and religious minorities are subjected the most to hate speech in Egypt. Finally, policies adjustments, recommended by experts and policy makers, in order to combat hate speech or at least to dilute its effects are suggested.